2021
DOI: 10.3390/ijms221910648
|View full text |Cite
|
Sign up to set email alerts
|

N-Acyl Dopamines Induce Apoptosis in Endometrial Stromal Cells from Patients with Endometriosis

Abstract: Endometriosis is characterized by the formation and development of endometrial tissues outside the uterus, based on an imbalance between proliferation and cell death, leading to the uncontrolled growth of ectopic foci. The potential target for the regulation of these processes is the endocannabinoid system, which was found to be involved in the migration, proliferation, and survival of tumor cells. In this paper, we investigated the effect of endocannabinoid-like compounds from the N-acyl dopamine (NADA) famil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 48 publications
(59 reference statements)
0
3
0
Order By: Relevance
“…Particularly, downregulated histamine degradation was associated with pregnancy complications, such as diabetes, miscarriage, and trophoblastic disorders [ 41 ]; Sirtuin deficiency impaired embryo invasion and decidualization [ 42 ]; ATM-deficient dams had lower implantation rates [ 43 ]; and excessive noradrenaline inhibited decidualization, embryo, and fetal development in mice [ 44 ]. Further, impaired decidualization may be caused by aberrant stromal cell differentiation, mediated by downregulated ID1 expression, [ 45 ] stromal cell apoptosis, induced by the N-acyl dopamine family [ 46 ], or attenuation of ribonucleotide reductase signaling, which impeded decidualization and implantation in mice [ 35 ]. Finally, significant repression of TSP1 mRNA expression was linked to unexplained recurrent spontaneous abortion (URSA) [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Particularly, downregulated histamine degradation was associated with pregnancy complications, such as diabetes, miscarriage, and trophoblastic disorders [ 41 ]; Sirtuin deficiency impaired embryo invasion and decidualization [ 42 ]; ATM-deficient dams had lower implantation rates [ 43 ]; and excessive noradrenaline inhibited decidualization, embryo, and fetal development in mice [ 44 ]. Further, impaired decidualization may be caused by aberrant stromal cell differentiation, mediated by downregulated ID1 expression, [ 45 ] stromal cell apoptosis, induced by the N-acyl dopamine family [ 46 ], or attenuation of ribonucleotide reductase signaling, which impeded decidualization and implantation in mice [ 35 ]. Finally, significant repression of TSP1 mRNA expression was linked to unexplained recurrent spontaneous abortion (URSA) [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…The effect of TEES-10 ® on the generation of reactive oxygen species (ROS) in the LPS-treated PDL cells was examined. We carried out 2′,7′-dichlorofluorescein (DCF-DA) staining in accordance with a precedent study [ 39 ]. PDL cells (8 × 10 3 cells/well) were cultured for 24 h and cultured further for 24 h in the media containing LPS (1 μg/mL) with or without TEES-10 ® (50 or 100 μg/mL).…”
Section: Methodsmentioning
confidence: 99%
“…In their original research, Gamisonia et al [3] investigated the effect of endocannabinoidlike compounds from the N-acyl dopamine (NADA) family on the viability of stromal cells forming ectopic and eutopic endometrium of patients with ovarian endometriosis. Their in vitro study demonstrated a dose-dependent cytotoxic effect of NADAs on stromal cells of eutopic and ectopic endometrium.…”
mentioning
confidence: 99%